The value of a law degree. Issue 2 (2nd April 2020) - Nicholson, Alex
ABSTRACT: Rising costs, vast increases in the proportion of young adults progressing to higher education and the introduction of alternative pathways to professional qualifications have in recent decades prompted some to argue that the "value" of an undergraduate law degree is diminished. Increasingly students, politicians, and society more widely appear to assess such value on an overly economic basis, focusing almost exclusively on employability and neglecting the wider and longer-term benefits for individuals, as well as for local and global communities. As the Solicitors Regulation Authority prepares to launch its new Solicitors Qualifying Examination (SQE), there is a risk that law schools may inadvertently erode existing value by placing too great an emphasis on preparing students for those centralised assessments and/or in how they respond to other market pressures. This paper draws on marketing theory to evaluate more holistically the potential value of a law degree, specifically in a post-SQE era. It is submitted that constructing resonating value propositions in relation to the wider and/or unique benefits of their programmes may help law schools to preserve, enhance and articulate value, thereby challenging the broader political rhetoric before it is too late. To this end, a new conceptual model is proposed. Abstract :